1997
DOI: 10.1097/00007632-199710010-00016
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of 438 Patients Treated Surgically for Lumbar Spinal Stenosis

Abstract: The results suggest that clear myelographic stenosis and no prior surgical intervention, no comorbidity of diabetes, no hip joint arthrosis, and no preoperative fracture of the lumbar spine are factors associated with a good outcome in surgical management of lumbar spinal stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
167
3
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(178 citation statements)
references
References 17 publications
5
167
3
3
Order By: Relevance
“…The finding that gender, BMI, previous back surgery, leg pain intensity, comorbidities, pain in the thoracic spine, somatization, treatment expectations, and walking distance were predictive of spinal surgery referral is in line with previous studies showing that they are also indicative of spinal surgery outcome [12,[19][20][21][22][23]. This can be interpreted as that surgeons are aware of and adhere to some extent to the current literature and (international) guidelines.…”
Section: Comparison With the Literaturesupporting
confidence: 88%
See 1 more Smart Citation
“…The finding that gender, BMI, previous back surgery, leg pain intensity, comorbidities, pain in the thoracic spine, somatization, treatment expectations, and walking distance were predictive of spinal surgery referral is in line with previous studies showing that they are also indicative of spinal surgery outcome [12,[19][20][21][22][23]. This can be interpreted as that surgeons are aware of and adhere to some extent to the current literature and (international) guidelines.…”
Section: Comparison With the Literaturesupporting
confidence: 88%
“…On the contrary, CLBP patients with comorbidities were found to be less likely to be referred to surgery than those without comorbidities. This too suggests that the surgeons referred in line with the current scientific evidence, as comorbidities are an important risk factor for surgery [12,19,21,22].…”
Section: Comparison With the Literaturementioning
confidence: 71%
“…Many spinal interventions appear to have excellent early post-operative results [2,3,14,40], but there is a temporal decline in benefit [21,35,41]. This would then indicate that conservative options may provide a viable option.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [17] showed poor results in the diabetic patients that may have been related to coexisting diabetic neuropathy. A recently published study by Airaksinen et al [1] concluded that diabetes was associated with poor surgical outcome.…”
mentioning
confidence: 99%